(3WHbGJ GdabgGA GdTGaYjIs - (3EHQGgje Hf Ydj Hf jhSa GdTjQGRj GdajQhRGHGOj , CHh ESMGb , LeGd GdOjf,J (B476 (3g` s ((3CHh HcQ Hf LeGYg s)
(3ChdgG (B:s
(3CNHQfG GdEeGe GdYdGeI JGL GdOjf Ch Gdjef RjO Hf GdMSjf CHh RjO GdcfOi PcQ abgGA GdUMGHI QVi Gddg Yfge hGYde Cf CcKQ CUMGH QShd Gddg Udi Gddg Ydjg hSde GdPjf UMHhg hdGRehg s
(3BNQgG (B:s
(3hUage GdbGVi CHh GdaQL GdbGai GdTjQGRi bd PcQJg ai CUMGH edc ced GdcJGH hGdMeO ddg Mb MeOg s
(3QhGjI CHj Gdjef RjO Hf GdMSf Hf RjO GdcfOi GdHZOGOi Yf MSf CHj GdMSf Ydi Hf gHg Gddg Hf YHO GdeSde GdcGJH Yf GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1100s
Keywords: (3GdJGQjNs